HUACHOS, PELUSAS, THIEVES AND BUGS: JUVENILE DELINQUENCY. TEMUCO 1929-1943 - Cárcamo Hernández, Ovidio (Revista de Historia Social y de las Mentalidades, 2011)
this paper it is centred in the typolo- gical research about minors who had  judiciary problems in a period included  from the years 1929 to 1943 in  temu- co  city and its surrounding.  on the  other hand it is an study which we can  recognize as a process leading to the  criminalization of the lower classes of  our society led by the elites who have  had the support of the judiciary and  criminalist theories in order to get this  end. For this purpose we describe the  socio-economic characteristic of the  teenagers who were processed and at the  end we described the process of punis- hment and re-education this adolescent  were submitted within the state of law.
Keywords: youth; delinquency; criminalization